Archeology and multidisciplinarity: a brief tour of the epistemological history of archaeological science and the challenges still pending: un breve recorrido por la historia epistemológica de la ciencia arqueológica y los desafíos aún pendientes - Lambri, Melania Lucila (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2022)
Archeology is presented to us today as an easily identifiable discipline thanks to the uniqueness of its object of study as well as the diversity of criteria and analytical procedures that it has been developing, maturing and re-evaluating throughout its disciplinary history. ; to the point that even today there are still debates around different theoretical and epistemological issues. This long process has also led Archeology to branch out into various sub-fields focused on addressing more specific themes and incorporating tools from other disciplines. Archaeometry and Historical Archeology are presented here as two clear exponents of the latter. They also express, and in a very notorious way today, a very interesting reality of archaeological practice: its inter, multi and even transdisciplinary nature. In fact, Archeology has managed to establish, from its earliest stages, strong contacts with other disciplines, both Human Sciences and Natural Sciences, which allow it to weave communication bridges between all of them. This capacity can be explained by the particularities of the objects that interest Archeology and by the influences it received from theoretical currents of the Philosophy of Sciences (FC) throughout its history. For this reason, it is proposed for this work to make a brief tour of the epistemological history of Archeology in which we will be able to identify the contributions of CF in the development of archeology as a science, observe the origins of inter-multidisciplinary studies in Archaeology, and contemplate the advantages and difficulties that persist to this day when carrying out joint work with other disciplines.